Giving Evil Its Due Judith Shklar's (Ambiguous) Cosmopolitan Realism and World Politics. (4th July 2022) - Royer, Christof
ABSTRACT: This article argues that Shklar's work can serve as a valuable source of inspiration to theorise the problem of humanitarian intervention. In contrast to some of her more sympathetic commentators, however, I will also problematise the tensions and ambiguities in Shklar's work. As such, my aim in this article is twofold: to demonstrate that Shklar's work can help us illuminate fundamental problems of world politics; and to demonstrate that the engagement with problems of world politics helps us to illuminate Shklar's work. My argument is that although Shklar's thought defies easy categorisation, her work can be understood as a 'cosmopolitan realism' as it combines realism's attentiveness to the realities and constraints of political life with the cosmopolitan insight that there are certain phenomena and experiences that are of genuinely universal concern. This 'cosmopolitan realism', however, is compromised by the conceptual ambiguity of Shklar's concept of cruelty and her undifferentiated use of the concept of evil. I argue that by 'giving evil its due', that is, by treating 'evil' as a distinctive phenomenon of life that must be distinguished from injustice, Shklar's cosmopolitan realism can be rectified and, indeed, serve as a valuable source for the creative theorisation of humanitarian intervention.